Protocol for profiling RNA m5C methylation at base resolution using m5C-TAC-seq - Xiaoting Zhang; Liang Lu; Chengqi Yi; Xiaoyu Li (STAR Protocols)
Summary: RNA 5-methylcytosine (m5C) is a widespread modification and plays a crucial role in gene expression regulation. Here, we present a protocol for transcriptome-wide m5C methylome profiling at base resolution using bisulfite-free m5C detection strategy enabled by ten-eleven translocation (TET)-assisted chemical labeling sequencing (m5C-TAC-seq). We detail steps for TET-assisted chemical labeling, library construction, and data analysis. m5C-TAC-seq enables accurate and robust m5C detection in various RNA species.For complete details on the use and execution of this protocol, please refer to Lu et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.